Flora associated with sweetpotato on Leyte island, Philippines - Klee, Renate; Koch, Werner (Annals of Tropical Research, 1994)
To characterize the flora associated with sweetpotato on Leyte island, Philippines, investigations were done in 14 sweetpotato fields and 9 fallows bordering the studied fields. The fallows were chosen to find out whether the bordering vegetation influenced the flora in sweetpotato fields. The studied sweetpotato fields and fallows were localized in three different sites which were mainly characterized by diverse vegetation types. Comparisons between the observed plant species and the three sites were done. Altogether, 215 different plant species were found in both the studied sweet potato fields and the fallows. In the sweet potato fields; 138 weed species could be identified, and 161 plant species (including 18 crop plants) were found in the fallows. To characterize the plant communities in the three sites, the registered plant species were summarized to diverse groups of vegetation.